ARKEOPRENEURSHIP SEBAGAI ALTERNATIF PEMANFAATAN HASIL PENELITIAN ARKEOLOGI MEMBANGUN PARIWISATA CAGAR BUDAYA NASIONAL - Asyhadi Mufsi Sadzali (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The results of archaeological research in Indonesia have been published in the form of research reports, scientific articles, seminar proceedings, and reference books, as well as in the form of audiovisuals. However, there is minimal absorption in the public sphere, and is considered difficult to accept, understand, and enjoy the general public. Research results should be used in various forms, and dimensions at all levels of society in line with the theory of the